Psychological features of emotional disorders in military personnel after mine-explosion injury during their medical-psychological rehabilitation - Yuliia Chumaieva; Victor Pahmurny; Vitaliy Fedorenko (Kazimierz Wielki University, 2023)
Research in the field of psychology of emotional disorders in military personnel with mine-explosion injuries intersects various disciplines such as psychology, medicine, military science, sociology, rehabilitation, etc. Unfortunately, there is currently no unified system, technology, and methodology for comprehensive medical-psychological rehabilitation of combatants, as preference is given to individual types - social, psychological, medical, physical, pedagogical, and the rehabilitation measures themselves have a fragmented nature. Therefore, the question arises about the justification of the effectiveness and measures of medical-psychological rehabilitation for military personnel who have participated in combat operations. The study involved 99 individuals - male military personnel aged 18 to 61 years, undergoing treatment and recovery in a medical institution. For the statistical analysis of the research results, factor, cluster analysis, and analysis of variance (ANOVA) were conducted. Based on the research results, three clusters were identified, differing in the average level of intelligence and characteristic diagnoses. It was found that individuals with higher intelligence more often experience adaptation disorders (33%), those with average intelligence - PTSD (27%), and those with low intelligence - organic emotional disorders (66%). The strongest correlation between verbal intelligence and the following personality profile scales was found: schizoid (-0.445, p≤0.01), psychasthenia (-0.436, p≤0.01), paranoia (-0.379, p≤0.01), depression (-0.371, p≤0.01), hysteria (-0.350, p≤0.01), psychopathy (-0.322, p≤0.01), hypomania (-0.251*), and hypochondria (-0.200, p≤0.05). The research results allow for the development of specific recommendations regarding psychological support and medical-psychological rehabilitation for military personnel who have experienced Mine-Explosion Trauma (MET). The obtained data can be utilized to enhance psychological training programs for military personnel in the event of possible traumatic situations, helping them better cope with emotional difficulties.